Interleukin 17 in early invasive breast cancer - Popović, Marina; Dedić Plavetić, Natalija; Vrbanec, Damir; Marušić, Zlatko; Mijatović, Davor; Kulić, Ana (Frontiers in Oncology, 2023)
Interleukin 17 (IL 17) has a key role in inflammatory responses. Increased serum concentrations of IL 17 have been reported in patients with different types of cancer. Some studies suggest antitumor activity of IL 17 while others speak in favor of its association with poorer prognosis. The lack of data on IL 17 behavior in vivo hinders the efforts to clarify the exact role of IL-17 in breast cancer patients and precludes the usage of IL 17 as potential therapeutic target. This study included 118 patients with early invasive breast cancer. The serum concentration of IL 17A was measured before surgery and during adjuvant treatment and compared with healthy controls. The correlation of serum IL-17A concentration and different clinical and pathological parameters, including IL 17A expression in the corresponding tumor tissue samples, was analyzed. Significantly higher serum concentrations of IL 17A were found in women with early breast cancer before surgery, but also during adjuvant treatment in comparison to healthy controls. Interestingly, no significant correlation to tumor tissue IL 17A expression was observed. There was a significant postoperative decrease of serum IL-17A concentrations even in patients with relatively lower preoperative values. A significant negative correlation was found between serum IL-17A concentrations and the tumor estrogen receptor expression. The results suggest that the immune response in early breast cancer is mediated by IL 17A, particularly in triple negative breast cancer. IL 17A mediated inflammatory response subsides postoperatively, but IL 17A concentrations remain elevated compared to the values in healthy controls, even after the removal of the tumor.